2013
DOI: 10.3168/jds.2012-6010
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal, neonatal, and rearing period mortality of dairy calves and replacement heifers in France

Abstract: Dairy calf and replacement heifer mortality in France was assessed by calculating mortality rates at 0 to 2d (calves), 3d to 1 mo (calves and heifers), 1 to 6 mo of age, and 6 mo of age to first calving (heifers) using the national identification database. Between birth and 2-d-old, 261,000 and 251,000 of the 3.56 and 3.43 million calves born in 2005 and 2006, respectively, died. The overall 0- to 2-d-old calf mortality rate was around 6.7%, which is similar to the low range of values reported in the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
9
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 28 publications
5
87
9
4
Order By: Relevance
“…These results are similar to that found previously (Svensson et al, 2006;Gulliksen et al, 2009;Torsein et al, 2011;Raboisson et al, 2013) confirming the need for more effective herd health measures to combat these disorders.…”
Section: Farmers´ Stated Reasons For On-farm Mortalitysupporting
confidence: 81%
See 4 more Smart Citations
“…These results are similar to that found previously (Svensson et al, 2006;Gulliksen et al, 2009;Torsein et al, 2011;Raboisson et al, 2013) confirming the need for more effective herd health measures to combat these disorders.…”
Section: Farmers´ Stated Reasons For On-farm Mortalitysupporting
confidence: 81%
“…This means that some farms achieve relatively low mortality in calves whereas some herds have very poor calf performance resulting in high mortality. This confirms the results of Raboisson et al (2013) who found high standard deviations for herd level mortality rates and concluded that it is possible for the farmers to achieve very low mortality rates also in animal categories known to have a high risk of mortality. Further studies should clarify the factors that determine the herd performance related with cattle mortality of different age groups.…”
Section: Risk Factorssupporting
confidence: 79%
See 3 more Smart Citations